The Development of Internet-based Economic Learning Media using Moodle Approach - Sari, Andika Puspita; Setiawan, Ananda (International Journal of Active Learning, 2018)
The objectives of research were to develop an internet-based economic learning media using MOODLE approach to improve the learning outcome of Senior High School Students in Bengkulu City. The method employed in developing an internet-based economic learning media with MOODLE approach was Borg & Galls Research and Development method encompassing four stages: preliminary study, development, trial, and dissemination. Trial staged employed Pretest-Posttest Control Group Design. The target of research was Senior High Schools in Bengkulu city with an independent sample test being the technique of analyzing data. From the result of research, the following conclusions could be drawn. Internet-based economic learning media using MOODLE approach had been developed successfully to improve the learning outcome of the 11th IIS (Social Sciences) graders of Senior High School.